Transferência dos esforços cisalhantes em juntas de pavimentos rígidos - Oliveira , Elisandra Miranda de (2008)
The joint is part of the constructive process of the rigid pavement. In its implementation the section of concrete located below it is weakened and eventually becoming the most vulnerable of the pavement can arise where the possible diseases that may affect their strength and durability. Despite the importance that the joint has in the life of the rigid pavement it is not exploited, and therefore became the main subject of this study. This work is an experimental study of the sawed joint in rigid pavement of concrete with evaluation of the transference of shear strength through the saweds joints. The experimental program consisted of test of fourteen simple concrete plates with sawed joint, and adoption of the following variable: presence of smooth dowel of Ø 12,5mm, variation of the length of dowel (500 mm, 400 mm and 300 mm), variation of the thickness of the plates (120 mm and 160 mm), variation of the strength to the compression of the concrete (20 MPa and 30 MPa) and of the type of used concrete (conventional and autoadensável). These plates had been supported on natural and assayed rubber layers with static shipment application in one of the sides of the together one until the rupture of the plate. The results had shown that: the use of dowel in these meetings increases the efficiency in the transference of efforts; the increase in the thickness of the plate increases the resistant capacity of the together one, the efficiency in the transference of efforts and possesss minors displacements of the plate during the application of the shipment; the dowel with reduced size are efficient, but the bars of 400 mm present resulted next to the one to the bar in commercial size, 500 mm; the plates in autoadensável concrete after the fissuration practically do not present contribution of the concrete in the transference of efforts for the intertravamento of aggregates; the sawed joint depth of the together one has influence in the way of rupture of the plate and tack relation enters the bar of transference and concret.